Factors Affecting the Recovery of Invertebrate Stocks From the 2011 Western Australian Extreme Marine Heatwave - Caputi, Nick; Kangas, Mervi; Chandrapavan, Arani; Hart, Anthony; Feng, Ming; Marin, Maxime; Lestang, Simon de (Frontiers in Marine Science, 2019)
The extreme Western Australia 2011 marine heatwave had a lasting effect on the marine ecosystem and after seven years, only parts of the ecosystem have showed good signs of recovery. After the heatwave, scallop fisheries in the Abrolhos Is. and Shark Bay were closed for 3-5 years, while the Shark Bay crab fishery was closed for 18 months; these fisheries at the centre of the heatwave have shown some improvement due to better protection of spawning stock and improved environmental conditions. Also at the centre of the heatwave, Roe’s abalone suffered a catastrophic mortality and has not recovered as spawning stock remains very low. The Perth abalone stock which was outside the peak heatwave area had a major stock reduction but remained opened with reduced catches. The heatwave had a marked indirect effect on brown tiger prawns in Exmouth Gulf due to loss of seagrass habitat. The heatwave also resulted in a decline in western king prawn recruitment in Exmouth Gulf, to the north of heatwave centre, but an improved recruitment in the cooler waters of Shark Bay. Western rock lobsters near the heatwave peak also appear to have been indirectly affected and have not recovered. Factors influencing the recovery rate from the heatwave appeared to be: species near their upper temperature range and/or sensitive to warming temperatures; spatial overlap between the warming event and species distribution; whether spawning stock was affected to the point of recruitment impairment; life-cycle duration of invertebrate (or habitat) species affected; and management intervention. This study provides a framework for managing the consequences of heatwaves on fisheries by highlighting the value of early identification of the event and its effect on fisheries and having flexible harvest strategies for early management intervention. This is particularly important as long-term increases in water temperatures will increase the frequency of marine heatwave events and the fisheries stocks would have less time for recovery